The incidentaloma of the thyroid - Dietlein, M.; Kobe, C.; Schmidt, M.; Schicha, H. (Nuklearmedizin - NuclearMedicine, 2005)
The incidentally detected thyroid nodule using sonography is described as incidentaloma; the most nodules have a diameter up to 1.5 cm. Sonography will detect thyroid nodules in more than 20% of the population in Germany. Epidemiological studies investigating the prevalence of malignancy in such incidentalomas are missing. The incidence of differentiated thyroid cancer is about 3 per 100,000 people and year. However, several monocentric studies have shown a prevalence of malignancy of up to 10% of the thyroid nodules in selected patients’ group. The histology did not found microcarcinomas only, but also small cancer with infiltration of the thyroid capsule, lymph node metastasis or multifocal spread. The studies were not designed for outcome measurement after early and incidental detection of small thyroid cancers. Hypoechogenity, ill defined borders, central hypervascularization or microcalcifications were used as combined criteria for risk stratification. The second method for risk stratification is scintigraphy and further tests are warranted for hypofunctioning nodule ≥1 cm. Additionally, the family history, patient’s age <20 years, former radiation of the neck, and measurement of calcitonin should be regarded. Without such a risk stratification selection for fine needle aspiration is impossible. Fine needle aspiration of non-palpable incidentalomas led to non-representative or unequivocal cytological findings in up to 40%. Because better outcome of incidentally detected small thyroid carcinomas is not proved and because sonography, scintigraphy and fine needle aspiration remain imprecise regarding dignity of incidentalomas, fine needle aspiration is not the standard for small, non-palpable thyroid nodules. Conclusion: For management of incidentaloma, sonographically unsuspicious, scintigraphically indifferent (nodules ≥1 cm) and without any risk factors in patients’ history, wait and see is justified when patient is informed about the problem.
Keywords: Incidentaloma; thyroid nodule; thyroid cancer; sonography; scintigraphy; fine needle aspiration; calcitonin